Combustion Characteristics Of Waste Cooking Oil Bio Diesel On Four Stroke Diesel Engine Using Additives - et. al., Surakasi Raviteja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transport is one of the petroleum and then pollutant most dependent sectors. A new generation of biofuels is under consideration, But usage should be reduced of current ones. The use of cooking oil can be interesting alternative fuels for diesel engines in some unique applications (i.e., public transportation, hybrid or marine propulsion, etc.). The Motor Bio-diesel diesel powered motor's performance and emission properties are highly affected by the ignition and combustion behavior. Combustion properties were studied in this analysis when the engine operating in two different dimensions (B20+1, B20+2) using a combination of different additive solvents (i.e. Isopropyl). The engine was found to have difficulty starting with pure cooking oil because of its high viscosity so that the combination with the diesel is finished. Biodiesel for performance testing was prepared and used for diesel engine.